Measuring Micronutrient Productivity in Integrated Aquatic Farming Systems for Nutrition Sensitive Agriculture - Ignowski, Liz; Belton, Ben; Ali, Hazrat (WorldFish, 2022)
The presentation showcased the survey results on measuring micronutrient productivity in integrated aquatic farming systems for nutrition sensitive agriculture in Bangladesh. The study suggested that integrated aquaculture-agriculture can be beneficial for both economic and nutritional productivity and can be used to identify and promote crop combinations to optimize both outcomes.